DESIGN AND IMPLEMENTATION OF A LABORATORY CAD / CAM - Rojas Lazo, Oswaldo (1998)
Design and Computer Aided Manufacturing commonly called CAD / CAM (Computer Aided Desing / Computer Aided Manufacturing) is an indispensable technology in production processes are subject to the high level of competitiveness in the domestic and international market, mainly because the companies need to abate their time designing and manufacturing with high quality